Low number of fixed somatic mutations in a long-lived oak tree. (December 2017) - Schmid-Siegert, Emanuel; Sarkar, Namrata; Iseli, Christian; Calderon, Sandra; Gouhier-Darimont, Caroline; Chrast, Jacqueline; Cattaneo, Pietro; Schütz, Frédéric; Farinelli, Laurent; Pagni, Marco; Schneider, Michel; Voumard, Jérémie; et al.
Abstract Because plants do not possess a defined germline, deleterious somatic mutations can be passed to gametes, and a large number of cell divisions separating zygote from gamete formation may lead to many mutations in long-lived plants. We sequenced the genome of two terminal branches of a 234-year-old oak tree and found several fixed somatic single-nucleotide variants whose sequential appearance in the tree could be traced along nested sectors of younger branches. Our data suggest that stem cells of shoot meristems in trees are robustly protected from the accumulation of mutations. Sequencing of nested branches from a 234-year-old oak tree reveals a low number of somatic mutations accumulating during its lifetime, implying that mechanisms are in place to reduce these potentially deleterious mutations during ageing.